Age at first treatment and immune tolerance to factor VIII in severe hemophilia - van der Bom, Johanna G.; Mauser-Bunschoten, Eveline P.; Fischer, Kathelijn; van den Berg, Marijke H. (Thrombosis and Haemostasis, 2003)
Findings from a recent study suggest that earlier start of treatment with factor VIII in patients with severe hemophilia is associated with a higher risk to develop inhibitors.We set out to assess the association between age of first administration of clotting factor VIII and the risk to develop inhibitors in infants with severe hemophilia A.This work was a cohort study, carried out in the national hemophilia treatment center. The study included eighty-one consecutive patients with severe hemophilia A who received their first dose of factor VIII between 1975 and 1998. Patients were followed until their last visit in 2001 or 2002.The average follow-up was 16 years (range 3-26). Persistent inhibitory antibodies developed in 12 of 81 patients (15%).Cumulative incidence at 100 exposure days was 34% (95% confidence interval 7-61%) in patients starting therapy before the age of 6 months, 20% (4-36%) in patients starting therapy between 6 months and 1 year, 13% (0-27%) in those starting therapy between 1 and 1.5 years, and 0% in those who started therapy beyond 1.5 years of age (p for trend 0.03).Our findings confirm that age of first factor VIII administration in children with severe hemophilia A is inversely associated with the risk to develop antibodies against factor VIII. The role of confounding factors such as the type of factor VIII mutation and environmental factors needs to be evaluated.
Keywords: Inhibitors; risk factors; age; cohort; immune tolerance